Co-effect of phosphorus and cadmium interaction on fraction distribution and accumulation of phosphorus in mangrove-sediment system. Issue 7 (3rd July 2017) - Du, Jingna; Yu, Junyi
ABSTRACT: Mangrove [ Kandelia obovata (S. L.)] seedlings were cultivated in rhizoboxes under different rates of phosphorus (P) and cadmium (Cd) level. The speciation distributions of P both in the rhizosphere and non-rhizosphere sediments were examined using sequential extraction procedures. P contents in different K. obovata (S.L.) tissues were also determined. Results showed that considerable differences existed in P speciation distribution between rhizosphere and bulk sediments. A higher proportion of iron-bound phosphate (Fe-P) was found in the rhizosphere sediments, while a relatively higher concentration of exchangeable phosphate (Ex-P) and Aluminum-bound phosphate was found in the bulk sediments. P accumulation in plant tissues was significantly positively correlated to Ex-P and Fe-P. Results indicated that root activities play an important role in the P cycling. And the coexistence of P and Cd induced higher P accumulation in mangrove plants. It is suggested that the root-induced chemical and biological changes in the rhizosphere environment play an important role in enhancing the bioavailability of soil P.